A Review on the Potential Millennial Farmers in Karanganyar District: Opportunities, Challenges, and Strategies - Usman, Irfan Budianto; Abidin, Ali Zainal (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
This study discusses the potential of millennial farmers in Karanganyar Regency. The purpose of this research is to see the opportunities that exist, know the challenges faced by millennial farmers, and understand the strategies used by millennial farmers in overcoming challenges in agricultural businesses. Karanganyar Regency was chosen as the research area because, according to census data from the Central Statistics Agency in 2023, Karanganyar Regency has the most significant number of Agricultural Business Households (RTUP) in Central Java Province. The approach used in this research is qualitative, with data obtained from primary data sources through questionnaires. This research involved a total of 104 respondents, namely millennial farmers aged 19-39 years who live in Karanganyar Regency. The data collection method used a closed questionnaire, while the data analysis method used was descriptive qualitative with content analysis. Source triangulation was used to measure data validity. The results showed that the potential of millennial farmers in Karanganyar Regency was quite effective because they were able to create broad market opportunities. In addition, they also managed to overcome challenges in the agricultural business through the strategies they developed.